2022
DOI: 10.1177/08854122221097977
|View full text |Cite
|
Sign up to set email alerts
|

Planning the Built Environment and Land Use Towards Deep Decarbonization of the United States

Abstract: Many governments, businesses, and institutions are committing to net zero greenhouse gas emissions by 2050, a goal and process known as deep decarbonization. Achieving this goal in the United States requires a national, economy-wide transformation in energy production and use in five sectors: electricity, transportation, industry, land-based carbon sinks, and buildings. All of these sectors interact with planning for the built environment and land use, so planning scholars and practitioners have many opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…However, for achieving net zero GHG emissions in buildings, it is necessary to undergo a widespread economic transition. In this particular, deep decarbonization methods place a lot of emphasis on buildings because they are substantial energy consumers and sources of GHG emissions [16]. Previous initiatives to improve building energy efficiency show some of the opportunities and limitations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, for achieving net zero GHG emissions in buildings, it is necessary to undergo a widespread economic transition. In this particular, deep decarbonization methods place a lot of emphasis on buildings because they are substantial energy consumers and sources of GHG emissions [16]. Previous initiatives to improve building energy efficiency show some of the opportunities and limitations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More climate scholarship in general and in particular scholarship that promotes decarbonization is needed. Energy planning as a specialty area has languished in the last decades, but the necessity of deep decarbonization argues for its resurrection, and new scholarship on the connections between energy provision, sustainability and land use is emerging (e.g., Hsu et al 2023; Randolph and Masters 2018). Existing planning research on decarbonization often overlooks policies associated with addressing embodied carbon , the GhG emissions associated with the extraction, manufacturing, installation, maintenance, and disposal of building materials—for instance, replacing high-carbon concrete with green infrastructure.…”
Section: Research In Support Of a Just Transitionmentioning
confidence: 99%
“…Previous studies have suggested that higher urban compactness, characterized by denser populations and more efficient land use, correlates with lower per capita GHG emissions [7][8][9][10][11][12][13][14][15][16]. This is often attributed to reduced vehicle usage in densely populated urban areas, where proximity to public facilities and efficient public transport systems diminish reliance on personal vehicles [17][18][19].…”
Section: Introductionmentioning
confidence: 99%